La historiografía contemporánea sobre la independencia en Centroamérica - Coralia Gutiérrez Álvarez (Nuevo mundo - Mundos Nuevos, 2009)
When considering the development of Central American historiography over the past half century, it is evident that the creole, liberal and positivist paradigms have been ceding ground to new ways of historical research on the independences, heavily influenced by the idea of modernity. Nevertheless, this article shows that, despite the abundant bibliography available and the new perspectives of the last two decades, political histories and elite histories keep on dominating the research on that subject.